Comparison of different kinds of nonviral vectors for gene delivery to human periodontal ligament stem cells - Yajing Wang; Shuhuan Shang; Chengzhang Li (Elsevier, 2015)
Background/purpose: Inducing human-periodontal-ligament-stem-cell (hPDLSC) differentiation by DNA transfection is a promising way for periodontal tissue engineering. However, there are only a few studies that focus on the introduction of foreign DNA into hPDLSCs by nonviral methods that are relatively safe. Hence, the major purposes of this study were to compare the transfection efficiency and toxicity of nonviral-gene-transfer methods on hPDLSCs, and to search for the best approach and optimal protocol for transferring genes into hPDLSCs using nonviral vectors. Materials and methods: The hPDLSCs were transfected by (1) Lipofectamine 2000, (2) polyethylenimine, (3) GBfectene-Elite transfection reagent, (4) X-tremeGENE HP DNA Transfection Reagent, and (5) Magnet-Assisted Transfection (MATra), compared to (6) lentiviral vectors harboring a green-fluorescent-protein gene. The transfection efficiency was measured by a fluorescence microscope and flow cytometry. Meanwhile, the cell morphology and growth status were observed to estimate the cytotoxicity. Results: Among these methods, the transfection efficiency of the former four methods was not very satisfactory (< 6%) compared to that of lentiviral vectors (positive control, 95%). However, MATra was the most effective nonviral method (11%). Moreover, the cellular toxicity was lower than that of the former four methods. Conclusion: The transfection efficiency of hPDLSCs with MATra was higher than the other nonviral transfection reagents in this study, but it was far less than the viral vectors. Saving from the interaction between the positive and negative charges, and increasing the opportunity of contact between the plasmid and the cytomembrane might be the key to enhancing the transfection efficiency for hPDLSCs in application of periodontal tissue engineering.